A Test of the Revised Minkov-Hofstede Model of Culture: Mirror Images of Subjective and Objective Culture across Nations and the 50 US States. (July 2021) - Minkov, Michael; Kaasa, Anneli
Various models of subjective culture (measures of self-reports) have been proposed since Hofstede's original work but none of them have been validated by showing that they have analogs in objective culture (measures of societal practices). Inspired by Bardi and Schwartz's discovery that Schwartz's individual-level circumplex values model has an exact equivalent in a model of behaviors, we develop a test for the purpose of validating models of culture. We apply this test to Minkov's revised two-dimensional variant of Hofstede's subjective-culture model, consisting of individualism-collectivism (IDV-COLL) and flexibility-monumentalism (FLX-MON) (formerly "long-term orientation"), as Fog recently found that an analog to this model incorporates and summarizes all major validated models and dimensions of national culture. We analyze national measures of important social practices associated empirically and theoretically with IDV-COLL and FLX-MON: transparency-corruption, gender equality, political freedom, road death tolls, homicide rates, family structures, innovation rates, and educational effort and achievement. These yielded close analogs to IDV-COLL and FLX-MON, with similar factor structures across nations and across the 50 US states, explicable in terms of IDV-COLL, FLX-MON, and life-history strategy (LHS) theories. Thus, subjective culture structures have mirror images in objective culture structures. This provides validation for our test, for the Minkov-Hofstede two-dimensional model of culture, for the use of nations and some sub-national political entities as units of cultural analysis, as well as for IDV-COLL, FLX-MON, and LHS theories.